Collaborative Governance for Management of Water and Air Pollution caused by Industrial Activities in Lamongan Regency, East Java - NAFISAH, Durrotun; SETYOWATI, Dewi Liesnoor; BANOWATI, Eva; PRIYANTO, Agustinus Sugeng (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021, 2021)
This study aimed to 1) analyze water and air pollution caused by industrial activities, 2) investigate water and air pollution management carried out by government agencies, 3) examine the Collaborative Governance process in controlling water and air pollution. This study used a qualitative method with a phenomenological approach. The data were collected using data collection techniques through in-depth interviews, field observations, and document studies. The results showed that 1) industrial activities in Lamongan Regency generated water pollution with a percentage of 17%, namely in Sidoharjo River and Dapur River, as well as a decrease in air quality due to many industries that did not adhere to air pollution control regulations, hence increasing CO 2 gas emissions by (72% ) or 3,712,849.07 Tons/Year, 2) reporting water and air pollution management done by submitting the related environmental documents through the SILILA Application ( Sistem Informasi Lingkungan Lamongan ), checking environmental documents, monitoring control, and socialization, 3) the execution of Collaborative Governance process in controlling water and air pollution is through five stages which include 1) public reports, 2) dialogue, 3) monitoring, 4) follow-up by governance, and 5) actions.